Identidad ambiental: múltiples perspectivas - Porras Contreras, Yair Alexander; Pérez Mesa, María Rocío (Revista Científica, 2019)
The purpose of this study is to characterize the literature that is being built on the world stage on environmental identity, taking as a timeline the academic production of the last 18 years in high impact databases. To fulfill this objective, we start with the formulation of two research questions: What is the scientific production (articles) related to research on environmental identity? What fields or areas have addressed research on environmental identity and what categories emerge? The results show that more than 50% of the literature on environmental identity is concentrated in two countries (the United States and the United Kingdom) and that in the analysis there are eight fields and/or areas of knowledge where environmental identity implies a sense of connection with nature, which involves skills, attitudes and values that emerge in the relationship with others.